Women’s profile with cervical lesions for HPV as for the risk factors for cancer of cervix - Bezerra, Saiwori J.S.; Gonçalves, Polyanna C.; Franco, Eugênio S.; Pinheiro, Ana K.B. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: we know that womb cancer is strictly related to the infection caused by human virus pappiloma. Many other elements, however, arealso responsible for malignant cell alterations, these being hazardous factors. Objective: people tried to identify these factors to cervical cancer inwomen suffering from HPV-caused cervical injuries. Methods: a quantity approach co-relational study developed in a STD and womb cancer pre-vention reference center made in the months of April and May, 2004, studied 37 women and identified the following: identity information, obstetric procedures, lifestyle, sexual behavior, reactive or infective conditions and clinic and laboratory exam results. Results: the average age studied was 30 years old, with an expressive amount of married or consensual-united women, 22 (60%). The major part, 73%, knew how to read and write and ear-ned less than 3 salaries. An inversely proportional relation in the numbers of pregnancy, births and aborts with the women of the research was noted.We consider that, in the analyzed people, among the factors that contribute to the growth of cervical cancer, the most common were: low economicclass level, more than two sexual partners in the whole life, the fact of not using condom, the use of contraceptives, the presence of a STD and thereduced number of pregnancies. Nutritional necessities, use of drugs, an early start of sexual life and the number of sexual partners were not toorepresentative factors in the data collected. Conclusion: we concluded that the research on other factors is helping with the recruitment of risk population, generating advances in an early detection of indicative injuries of womb cancer.